2012
DOI: 10.3389/fpsyt.2012.00091
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Individual Variation during Transcranial Direct Current Stimulation and Normalization of Dose Using MRI-Derived Computational Models

Abstract: Background: Transcranial Direct Current Stimulation (tDCS) is a non-invasive, versatile, and safe neuromodulation technology under investigation for the treatment of neuropsychiatric disorders, adjunct to rehabilitation, and cognitive enhancement in healthy adults. Despite promising results, there is variability in responsiveness. One potential source of variability is the intensity of current delivered to the brain which is a function of both the operator controlled tDCS dose (electrode montage and total appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
324
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 374 publications
(359 citation statements)
references
References 36 publications
(52 reference statements)
18
324
0
1
Order By: Relevance
“…Despite the abundance of research reporting tDCS effects on plasticity, in recent years large inter-individual variability in response to tDCS has been recognized (Datta et al 2012, Puri et al 2015, Wiethoff et al 2014. For example, Fujiyama et al observed that approximately 20% of participants (8 out of 39) did not show the expected corticospinal excitability increase following tDCS with anode placed over M1.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the abundance of research reporting tDCS effects on plasticity, in recent years large inter-individual variability in response to tDCS has been recognized (Datta et al 2012, Puri et al 2015, Wiethoff et al 2014. For example, Fujiyama et al observed that approximately 20% of participants (8 out of 39) did not show the expected corticospinal excitability increase following tDCS with anode placed over M1.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, despite increasing sophistication in these computational models (Wagner et al, 2004;Datta et al, 2009;Sadleir et al, 2010;Parazzini et al, 2011;Datta et al, 2012;Minhas et al, 2012;Datta et al, 2010;Wagner et al, 2007;Datta et al, 2011;Dmochowski et al, 2013;Luu et al, 2016), none of these model predictions have been directly validated to-date. Early validation efforts for simple spherical models used ex vivo recordings (Rush and Driscoll, 1968), surface recordings (Burger and Milaan, 1943) or in vivo recordings in simian (Hayes, 1950).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of inter-subject factors have been identified as influencing tDCS including anatomical structure Datta et al, 2012) age (Fujiyama et al, 2014;Moliadze et al, 2014), and potentially even genetic profile (for review see Li et al (2015)). …”
Section: Introductionmentioning
confidence: 99%